Influence of flaky aggregate on marshall properties for asphaltic concrete AC20 mixture - Abd. Karim, Zaini (2013)
Aggregate is the most important material that been used widely in the road pavement construction together with asphalt binder. The problem scenario is referring the road problems such as deformation, surface defect, cracks and edge defects. Basically, these study is absolutely focusing on influence of flaky aggregate on Marshall Properties for Asphaltic Concrete AC 20 mixture. In order to evaluate these problem, laboratory tests will be carried out are Aggregate Physical Test, Asphalt Test and Marshall Stability Test. The optimum asphalt content (OAC) needs to be determined before preparing samples to run the test by Marshall Properties to obtain the stiffness, stability, density, flow, VTM and VFB. The (OAC) was determined by using bitumen content of 4.5%, 5.0%, 5.5%, 6.0% and 6.5% for stage 1 which are 45 sample were prepared. For stage 2, verification sample was prepared by using (OAC) obtained. This sample used to verify the (OAC) whether it will meet the specification or not at the same time, nine samples were prepared at this stage, samples were mixed together with (OAC) obtained and aggregate. All samples were conducted to Stability Test again. The result shows, the increasing of flaky aggregates on proportion resulting the decreasing value of stability, stiffness VTM and VMA. The decreasing of flaky aggregates on proportion resulting the increasing value of flow and VFB.